Phylogeny, phylogeography, and evolution in the Mediterranean region: news from a freshwater mussel (Potomida, Unionida) - Froufe, Elsa (2018)
The Potomida genus (Bivalvia, Unionida) has a Circum-Mediterranean distribution and like other freshwater mussel species, its populations have suffered dramatic declines. Although this genus is currently considered as monotypic, it has a long history of taxonomic revisions and presently many aspects of its systematics and evolutionary history are unclear. We sampled a total of 323 individuals from 39 different sites across the Potomida genus distribution, and sequenced two mitochondrial (16S rDNA and Cytochrome c Oxidase Subunit I) and one nuclear (28S rDNA) genes to clarify its phylogeny and phylogeographic history. Our results show that the genus includes two well-supported clades, one comprising solely the western Mediterranean species Potomida littoralis, and the other including two eastern Mediterranean species, the Greek endemic P. acarnanica and the Anatolian and Middle Eastern P. semirugata. We suggest that Potomida started radiating during the upper Miocene, and that both vicariance and dispersal events shaped the diversification and distribution of the genus along the Mediterranean region. P. littoralis is further divided in two mitochondrial lineages, one restricted to Europe and the other occurring mostly in North Africa. Moreover, some European basins present both lineages in sympatry. The conservation status of the three recognized species should be reevaluated, particularly P. acarnanica, since it is restricted to two Greek river basins presenting a high risk of extinction. Overall, our results clarify some important gaps in knowledge concerning the phylogeny, phylogeography and evolution of the Potomida genus in the Mediterranean region with important taxonomical, ecological and conservational implications.